Vous êtes sur la page 1sur 18

# :

:1
f -1 f(x) = -2x + 1 :
-f(1/2), f(1), f(0) :
- ) (D f .
- D(1/2;0) , C(-1;1) , B(1;-1), A(0;1) : (.)D
M(x;y) -2 ) (AB M : A . B
- :

y yA
yB yA

x xA
xB xA

- y = -2x + 1
2

-1f(x) = -2x + 1 :
-
)(D

f(0) = -2 x 0 + 1 = 1 -

f(1) = -2 x 1 + 1 = -1
f(1/2) = -2 x (1/2) +1 = 0

## f(1) = -1 : ) B(1;-1 )(D

f(-1) = 3 : ) C(-1;1 )(D
f(1/2) = 0 : ) D(1/2;0 )(D

- 2-

) y y A f (x) f (x A

x xA
x xA

2
yB yA
) f (x B ) f (x A

xB xA
xB xA

A B M ) (D -2 .f

y yA
2
x xA

y 1
2
x
y 2x 1

) (D ) M(x;yy = -2x + 1 :

) (O,I,J .

) (D
:

(D): y = mx +p

m ). (D
p .

1
) A(xA;yA ) B(xB;yB
) (D y = mx + p :
:

yB yA
m
xB xA

xA xB

x . y
B
xB
yB

A
xA
yA

x
y

(D): y = 2x +3

3 ) (D 2
:
B
1
5

A
0
3

x
y

10

) (D

)(D

11

:2
) (O,I,J .

(D): y = mx + p

)D(: y = mx + p

A B ) (D A(1;y1) : )B(0;y2
A B ) (D A)1;y3) : )B)0;y4
-1 y1 y2 y3

.y4

-2 BAAB ))D( // (D
12

) (O,I,J .
(D): y = mx + p

)D(: y = mx + p

-1 y1 = m + p y2 = p y3 = m + p y4 = p

-2

## ) B'A '(1; m )BA(1; m

BABA

))BA( // (BA
))D( // (D
13

2
) (O,I,J .
) (D ( )D :

(D): y = mx + p

)D(: y = mx + p

((D) // )D

( (D) // )D

m = m

m = m

14

) (d2 )(d1
:
): (d1

y = ax + b

y = a1 x + b1

) P(xp;yp )(d2

) (d1 ).(d2
P ) (d2 b ).(d2
15

(D): y = 2x + 3 , )D( : y = 2x - 3

.
()D

)(D

16

3
) (O,I,J .
) (D ( )D :
(D): y = mx + p

)D(: y = mx + p

m m = -1

()D( )D

m m = -1

()D( )D

17

) (d2 )(d1
(d1): y = a1x + b1
(d2): y = a2x + b2
-1
a1 a2 = -1

)(d1) (d2

a1 .a2
) (d2 a2 x y )(d2
).(d2
18